Cattle Rumen Microorganisms Hydrolysis for Switchgrass Saccharification, Volatile Fatty Acids and Methane Production - Florendo, P. DC.; Sharma-shivappa, R.; Fellner, V. (International Journal of Agricultural Technology, 2018)
This study had determined the effect of duration on processes of saccharification, volatile fatty acids and methane gas in switchgrass hydrolysis using cattle rumen microorganisms. Inputs to fermentation were 2g milled switchgrass, 10ml strained Holstein cattle rumen fluid and 88ml distilled water with headspace using a 150 ml capacity serum bottle. Hydrolysis pH was neutralized with alkaline solution; sealed fermentation bottles with butyl cap and aluminium crimp and incubated at 37oC with periodic shaking of 75 revolutions per minute. Fermentation was stopped at duration 6, 14, 38, 44, 68 and 92 hours. Contents of saccharides in hydrolysates were evaluated using High pressure liquid chromatography and Dinitrosalycilic acid assay while volatile fatty acids and methane gas produced at different durations were estimated by Gas chromatography. Results showed duration’s significant effect on saccharification hydrolyzed carbohydrates, highest rate of 3.97 %/hr at 6 hr and highest carbohydrates conversion efficiency of 71.2% at 92 hr(p>0.05). Acetate, iso-butyrate and butyrate were gradually produced at different periods while volatile fatty acids total content of 14.35mM obtained at 92 hr implied duration’s significant impact on volatile fatty acid production in switchgrass using cattle rumen microbes(p>0.05). Methane gas showed significant and highest yield of 16.38mM/ ml at 44 hr and lowest yield at 92 hr duration(p>0.05). In conclusion, switchgrass hydrolysis using cattle rumen microorganisms’ fermentation processes produce hydrolyzed carbohydrates, acetate, isobutyrate and butyrate, total volatile fatty acids and methane gas. Duration of the pretreatment of switchgrass with rumen microbes is a vital factor that affects the processes of saccharification, volatile fatty acids and methane production. Information generated in the study are essential in the development of rumen microorganisms as pretreatment of switchgrass as animal feeds, biomass for bioethanol, volatile fatty acids and methane gas production.